2014
DOI: 10.3390/ijerph110404292
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination Detection in Water Resources: Interest of Current Optical Methods, Trends and Needs in the Context of Climate Change

Abstract: Microbial pollution in aquatic environments is one of the crucial issues with regard to the sanitary state of water bodies used for drinking water supply, recreational activities and harvesting seafood due to a potential contamination by pathogenic bacteria, protozoa or viruses. To address this risk, microbial contamination monitoring is usually assessed by turbidity measurements performed at drinking water plants. Some recent studies have shown significant correlations of microbial contamination with the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 99 publications
(112 reference statements)
0
42
0
3
Order By: Relevance
“…Characteristics of rainfall and runoff, such as rainfall pattern, effective rainfall volume, and overland flow velocity, have been identified as some of the most critical factors affecting transport of pathogens from the land surface (Funari, et al 2012, Bhavnani, et al 2014, Jamieson, et al 2004, Ferguson, et al 2005, Jung, et al 2014, Tsihrintzis and Hamid 1997). However, the relationship of these factors with in-stream pathogen concentrations across sites is complex.…”
Section: Modeling Pathogen Transport During Floodsmentioning
confidence: 99%
“…Characteristics of rainfall and runoff, such as rainfall pattern, effective rainfall volume, and overland flow velocity, have been identified as some of the most critical factors affecting transport of pathogens from the land surface (Funari, et al 2012, Bhavnani, et al 2014, Jamieson, et al 2004, Ferguson, et al 2005, Jung, et al 2014, Tsihrintzis and Hamid 1997). However, the relationship of these factors with in-stream pathogen concentrations across sites is complex.…”
Section: Modeling Pathogen Transport During Floodsmentioning
confidence: 99%
“…Nevertheless, some studies indicated that river bed sediments could be significant reservoirs of certain bacterial pathogens. These could get re-suspended when the river flow reaches a critical level (Brookes et al, 2004; Jung et al, 2014; Frey et al, 2015). These reservoirs can thus be significant in the global epidemiology of waterborne pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…There are several substrates available in the literature for the detection of these enzymes, and interested readers can refer elsewhere. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]45,50,[56][57][58] We have selected a combination (similar to the one used in MWK 45 ) of Red-Gal and MUG as substrates for the enzymes β-D-galactosidase and β-Dglucuronidase, thereby enabling simultaneous detection of total coliform and E. coli. Red-Gal was used as the substrate to target β-Dgalactosidase produced by total coliform to yield 4-chloro-indoxyl, which upon dimerization produces a red colored indigo derivative.…”
Section: Simultaneous Detection Of Totalmentioning
confidence: 99%
“…Immunological methods [11][12][13][14][15][16][17][18] target specific antigens of bacteria using specific antibodies. The indicator bacteria releases an antigen which can be detected using antigen-antibody interaction.…”
Section: Gunda and Mitra (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation